Pembelajaran Berbasis Masyarakat di SLTP Alternatif Qaryah Thayyibah Salatiga - Moh Hasim (Analisa: Journal of Social Science and Religion, 2010)
SLTP Alternative Qaryah Tayyibah Salatiga as community-based schoolis able to provide answers to the weak access of the poor to get quality educationin the middle of limitation ability of government give competent education to society.The Focus of the problems examined in this research is how the  implementation of community-based learning in SLTP Qaryah Alternative Thoyyibah.This Research find the existence of enableness of local potency  and source supported by system study of contekstual which is student centre as educative subjek which supported by society citizen participation, can send SLTP Alternative of Qaryah Thayyibah become certifiable school.Keywords : learning, community participation